Waist Circumference as a Screening Tool for Metabolic Syndrome in Resource-Limited Countries - Al Khani, Abdullah Murhaf; Khalifa, Mohamed Abdelghafour; Basha, Amjad Chamsi; Billah, Syed Muhammad Baqui (International Journal of Human and Health Sciences (IJHHS), 2024)
Background: The prevalence of metabolic syndrome (MetS) has been increasing, especially in developing countries. It is important to have an easy to perform and inexpensive screening system in such resource-bound countries. Objective: To compare the value of waist circumference over body mass index (BMI) for a better assessment of MetS. Methods: In this cross-sectional study, we collected data from 492 participants residing in both urban and rural areas of Bangladesh, as a secondary dataset from another previous cross-sectional study. Receiver operating characteristic (ROC) analyses were performed to construct three curves that illustrate the sensitivity and specificity of waist circumference vs. BMI in predicting the presence of MetS. Results: The overall prevalence of MetS was 38.6% and was higher among males. In addition, waist circumference showed a consistent strong statistical association with the ATP III components. More importantly, diagnostic accuracy analysis of waist circumference showed a sensitivity and a specificity of 72.6% and 68.3% in females and 88% and 85%, in males, respectively. In contrast, BMI resulted in a sensitivity and a specificity of 65.8% and 62.9% in females and 76.1% and 64%, in males, respectively. Conclusion: Waist circumference could be used as good predictor of MetS. Clinicians should use this information in their practice to ease the financial burden associated with diagnosing MetS. International Journal of Human and Health Sciences Vol. 08 No. 03 Jul’24 Page: 283-288